Konversi Agama dalam Perspektif Psikologi Pendidikan Islam - Dewi, Rachma Rusdiana; Miftahurrohman, Miftahurrohman; Rohimah, Siti (TSAQOFAH, 2025)
The phenomenon of religious conversion is a multidimensional process involving theological, psychological, and social aspects. In the context of Islam, conversion is understood not merely as the verbal declaration of the shahada, but as a comprehensive transformation encompassing spiritual awareness, value internalization, and a committed adherence to Islamic teachings. This study aims to analyze the process of religious conversion through the lens of Islamic educational psychology, emphasizing conversion as a form of tarbiyah nafsaniyah, a transformative journey involving cognitive, affective, and psychomotor changes. Utilizing a qualitative, library-based approach, the research identifies key factors that trigger conversion, including identity crises, the search for life’s meaning, spiritual experiences, and social influences. The findings indicate that the conversion process requires empathetic and context-sensitive educational guidance, along with support from an inclusive environment to strengthen the sustainable development of Islamic identity. Islamic educational psychology plays a crucial role in guiding this transformation in a humane and holistic manner. These insights contribute both theoretically and practically to the development of value-oriented strategies for nurturing muallaf, grounded in personal experience and spiritual growth.